Effects of Aging and Aging Method on Physicochemical and Sensory Traits of Different Beef Cuts - Kim, Minsu (Food Sci Anim Resour, 2019)
Wet and dry aging methods were applied to improve the quality of three different beef cuts (butt, rump, and sirloin) from Hanwoo cows (quality grade 2, approximately 50-mon-old). After 28 d of wet aging (vacuum packaged; temperature, 2±1°C) and dry aging (air velocity, 2–7 m/s; temperature, 1±1°C; humidity, 85±10%), proximate composition, cooking loss, water holding capacity, shear force, color, nucleotides content, and sensory properties were compared with a non-aged control (2 d postmortem). Both wet and dry aging significantly increased the water holding capacity of the butt cuts. Dry aging in all beef cuts induced lower cooking loss than that in wet-aged cuts. Shear force of all beef cuts was decreased after both wet and dry aging and CIE L*, a*, and b* color values in butt and sirloin cuts were higher in both wet and dry aging (p<0.05) groups than those in the non-aged control. Regardless of the aging method used, inosine-5′-monophosphate content among beef cuts was the same. The sensory panel scored significantly higher values in tenderness, flavor, and overall acceptability for dry-aged beef regardless of the beef cuts tested compared to non- and wet-aged cuts. In addition, dry-aged beef resulted in similar overall acceptability among the different beef cuts, whereas that in wet-aged meat was significantly different by different beef cuts. In conclusion, both wet and dry aging improved the quality of different beef cuts; however, dry aging was more suitable for improving the quality of less preferred beef cuts.